Analisis Upaya J&T Cargo Marapalam Padang Dalam Melakukan Perubahan Di era Teknologi Digital - Riziq, Awam Mukhatam; Fitri, Nadilla Silva; Syafputri, Niati; Rizki, Muhammad; Putra, Ramdhani Bayu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This Community Service aims to find out J&T Cargo efforts to make changes in the era of digital technology. Change is the change of situation from the old to the new. Change is a difference in circumstances from a certain phase to another phase. Changes made by J&T Cargo Padang in digital technology such as e-commerce platforms. for example shopee, lazada, olx, etc. with the development of this technology, it has made quite good changes by increasing the delivery of goods, as well as the payment system with mobile banking and QRIS barcodes, so that payments from both customers and J&T Cargo are easier and faster, there is a COD (Cash On) system Delivery) check first, and there is a new system, namely, a real time or recession system. This article was prepared by observation, collecting data in interviews, and documentation. The research results show that J&T Cargo Marapalam Padang adheres to the Emergent Change theory, which shows that J&T Cargo is able to make critical or sudden changes by having to adapt and this is a must considering current technological developments which provide quite large advantages and benefits.